Ecrh-related technologies for high-power and steady-state operation in LHD - Shimozuma, T; Takahashi, H; Kubo, S; Yoshimura, Y; Igami, H; Takita, Y; Kobayashi, S; Ito, S; Mizuno, Y; Idei, H; Notake, T; Sato, M; et al. (2010)
The electron cyclotron resonance heating (ECRH) system on the Large Helical Device (LHD) has been in stable operation for ∼11 yr in numerous plasma experiments. During this time, many upgrades to the system have been made, such as reinforcement of the gyrotron tubes, modification of the power supply depending on gyrotron type, and increase in the number of transmission lines and antennas. These efforts allow the stable injection of millimeter-wave power in excess of 2 MW. In parallel, various transmission components were evaluated, and antenna performance was confirmed at a high power level. The coupling efficiency of the millimeter wave from the gyrotron to the transmission line and the transmission efficiency through the waveguide were further improved in recent years. The feedback control of the wave polarization has also been tried to maximize the efficiency of wave absorption. The gyrotron oscillation frequency was reconsidered in order to extend the flexibility of the magnetic configuration in plasma experiments. The development of 77-GHz gyrotrons with the output of 1 MW per few seconds in a single tube is currently taking place in collaboration with the University of Tsukuba. Two such gyrotron tubes already have been installed and were used for plasma experiments recently. An ECRH system with a capability of the steady operation is required, because the LHD can continuously generate confinement magnetic fields using superconducting magnets. Not only the gyrotron but also the transmission system and components must withstand continuous power operation. Further acceleration of both the power reinforcement and a steady-state capability will allow the sustainment of high-performance plasmas.